Altered connectivity of the default mode network in cognitively stable adults with Down syndrome: "Accelerated aging" or a prelude to Alzheimer's disease?. Issue 1 (20th May 2021) - Rosas, H. Diana; Lewis, Lydia R.; Mercaldo, Nathaniel D.; Nasr, Shahin; Brickman, Adam M.; Siless, Viviana; Yassa, Michael; Sathishkumar, Mithra; Lott, Ira; Schupf, Nicole; Silverman, Wayne; Lai, Florence; et al.
Abstract: Introduction: Most individuals with Down syndrome (DS) have the neuropathological changes of Alzheimer's disease (AD) by age 40 and will have developed dementia by age 60. Alterations of the intrinsic connectivity of the default mode network (DMN) are associated with AD in the neurotypical population. In this study, we sought to determine whether, and how, connectivity between the hubs of the DMN were altered in cognitively stable adults with DS who did not have evidence of either mild cognitive impairment or AD. Methods: Resting state functional MRI scans were collected from 26 healthy adults with DS and 26 healthy age‐matched non‐DS controls. Nodes comprising the DMN were generated as ROI's (regions of interest) and inter‐nodal correlations estimated. Results: Analysis of intra‐network connectivity of the DMN revealed anterior‐posterior DMN dissociation and hyper‐ and hypo‐connectivity, suggesting "accelerated aging" in DS. Discussion: Disruption of the DMN may serve as a prelude for AD in DS.